Ultra-high pitch chest computed tomography at 70 kVp tube voltage in an anthropomorphic pediatric phantom and non-sedated pediatric patients: initial experience with 3rd generation dual-source CT - Henzler, Claudia; Henzler, Thomas; Haubenreisser, Holger; Meyer, Mathias; Janssen, Sonja; Schönberg, Stefan; Neff, Wolfgang; Weis, Meike (Zeitschrift für medizinische Physik, 2016)
Purpose: Minimizing radiation dose while at the same time preserving image quality is of particular importance in pediatric chest CT. Very recently, CT imaging with a tube voltage of 70 kVp has become clinically available. However, image noise is inversely proportional to the tube voltage. We aimed to investigate radiation dose and image quality of pediatric chest CT performed at 70 kVp in an anthropomorphic pediatric phantom as well as in clinical patients. Methods and Materials: An anthropomorphic pediatric phantom, which resembles a one-year-old child in physiognomy, was scanned on the 3rd generation dual-source CT (DSCT) system at 70 kVp and 80 kVp and a fixed ultra low tube-current of 8 mAs to solely evaluate the impact of lowering tube voltage. After the phantom measurements, 18 pediatric patients (mean 29.5 months; range 1-91 months; 21 examinations) underwent 3.2 high-pitch chest CT on the same DSCT system at 70 kVp tube voltage without any sedation. Radiation dose and presence of motion artifacts was compared to a retrospectively identified patient cohort examined at 80 kVp on a 16-slice single-source-CT (SSCT; n=15; 14/15 with sedation; mean 30.7 months; range 0-96 months; pitch=1.5) or on a 2nd generation DSCT without any sedation (n=6; mean 32.8 months; range 4-61 months; pitch=3.2). Results: Radiation dose in the phantom scans was reduced by approximately 40% when using a tube voltage of 70 kVp instead of 80 kVp. In the pediatric patient group examined at 70 kVp age-specific effective dose (ED; mean 0.5±0.2 mSv) was significantly lower when compared to the retrospective cohort scanned at 80 kVp on the 16-slice-SSCT (mean ED: 1.0±0.3 mSv; p<0.0001) and also considerably lower when compared to the cohort scanned at 80 kVp on the 2nd generation DSCT (mean ED: 0.9±0.5 mSv). None of the prospective, sedation-free CT examinations showed any motion artifacts whereas 13/15 examinations of the retrospective patient cohort scanned at 80 kVp with a pitch of 1.5 showed motion artifacts. Conclusion: 3.2 high-pitch chest CT performed with 70 kVp significantly reduces radiation dose when compared to 80 kVp while at the same time provides good image quality without any motion artifacts even without sedation.